The Effect of Male Outmigration on Women’s Empowerment in Nepal - Sapkota, Chandan; Wie, Dainn (Migration Letters, 2024)
Outmigration is dominated by men in Nepal, where gender equality is an imminent development goal. In this study, we ask whether male-dominant outmigration affects the empowerment of women left behind using two rounds of survey data collected in 2006 and 2011. We address endogeneity in migration using instrumental variable estimation and provide empirical evidence that married women in households with male outmigrants are less likely to be in polygamous relationships and are more likely to have the final say on their own health issues. However, these women are less likely to have the freedom to visit their family or relatives. We show that male outmigration increases married women’s cohabitation with their parents-in-law and conjecture that the decrease in mobility is due to such living arrangements.